2002
DOI: 10.1034/j.1399-6576.2002.460508.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ondansetron, tropisetron or metoclopramide to prevent postoperative nausea and vomiting: a comparison in high‐risk patients undergoing thyroid or parathyroid surgery

Abstract: In the initial period, the incidence of PONV was lower after premedication with oral tropisetron than after ondansetron or metoclopramide. Considering the entire 24-h postoperative period, the incidence of PONV was the same after all three premedications, but the incidence of vomiting was lower after oral ondansetron and tropisetron than after metoclopramide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
0
22
2
Order By: Relevance
“…We found sedation in 3 patients and hypotension in 1 patient in this study. Droperidol has been reported to induce sedation, hypotension, and extrapyramidal side effects [11,14]; we found sedation in 5 patients, hypotension in 4 patients, and headache in 1 patient in this group.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We found sedation in 3 patients and hypotension in 1 patient in this study. Droperidol has been reported to induce sedation, hypotension, and extrapyramidal side effects [11,14]; we found sedation in 5 patients, hypotension in 4 patients, and headache in 1 patient in this group.…”
Section: Discussionmentioning
confidence: 61%
“…Acceptable medications for antiemetic prophylaxis must have a duration of action covering the perioperative period and have minimal side effects [10,11]. The optimum drug dosage for PONV prophylaxis with minimal side effects has been studied using 0.15–0.25 mg/kg i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thyroid surgery, the selective 5-hydroxytryptamine type 3 (5-HT 3 ) receptor antagonists granisetron, ondansetron, and tropisetron are considered superior to traditional antiemetic agents [8,9]. However, to date, the efficacies of these three different serotonin antagonists have not been compared.…”
Section: Introductionmentioning
confidence: 97%
“…49 Dolasetron 12.5 mg was also found to have similar efficacy to ondansetron 4 mg with a similar side effect profile for the prevention of PONV. 50,51 In an earlier study, dolasetron 50 mg had similar efficacy to ondansetron 4 mg. 52 Similarly, in a multicentre trial, it was demonstrated that 2 mg tropisetron intravenously had similar efficacy and side effect profiles to those of ondansetron 4 mg. 53 This was confirmed in another two trials comparing iv tropisetron 5 mg with ondansetron 4 mg and oral tropisetron 5 mg with ondansetron 16 mg. 54,55 Fujii and colleagues compared the antiemetic efficacy of granisetron 2.5 to 3 mg and ramosetron 0.3 mg in three studies. There was no difference between the two agents in achieving a complete response (no PONV and no antiemetic rescue) during the first 24 hr postoperatively.…”
Section: Receptor Antagonistsmentioning
confidence: 99%